The relationship between M-learning and Self-regulated-learning in the context of vocational education (R&E-SOURCE, 2025)
This article focuses on the link between mobile learning (M-learning) and self-management in the context of vocational education. It first discusses the importance of innovative technologies in vocational education that can improve the quality of higher education in the 21st century. The paper presents the results of a systematic mapping exercise carried out in the context of M-learning and the subsequent categorisation of innovative technologies. M-learning offers many benefits, but it is important to pay attention to potential risks such as overuse of technology and distraction. The paper emphasizes self-regulated learning and recommends the promotion of students' self-regulatory skills in M-learning environments. Recent research in the area of self-regulated learning of university students and blended learning versus traditional teaching offers interesting results and suggests that M-learning can be an effective tool both in terms of professional learning and for promoting self-regulation, but it requires communication, a systematic approach and collaboration between teachers and students.